Analisis Karakteristik dan Diagnosa Keperawatan Pasien HIV/AIDS dengan Infeksi Oportunistik: A Comprehensive Analysis of Patient Characteristics and Nursing Diagnoses in Individuals Living with HIV/AIDS and Experiencing Opportunistic Infections - Hanim, Risyda Zakiyah (Lentora Nursing Journal, 2025)
ABSTRACT Background: Human Immunodeficiency Virus (HIV) is a viral infection that compromises the immune system by targeting and depleting lymphocytes. Individuals living with HIV/AIDS are particularly vulnerable to opportunistic infections due to their weakened immune response. Objective: This study aims to analyze the characteristics of HIV/AIDS patients with opportunistic infections who are undergoing antiretroviral therapy (ART). Method: A descriptive-analytical research design was employed to examine the characteristics of HIV/AIDS patients. The sampling method used was purposive sampling. Data were collected using a demographic questionnaire and analyzed using SPSS software. Results: Among HIV/AIDS patients receiving ART, a significant proportion (83.3%) had a history of opportunistic infections. Most respondents were adults (86.7%), male (63.3%), and married (43.3%). The majority had attained a secondary level of education (50.0%) and were employed (80%). Conclusion: The most prevalent nursing diagnoses among respondents included nutritional deficits, treatment non-compliance, and lack of knowledge. A substantial number of participants continued to experience opportunistic infections despite undergoing antiretroviral therapy.